2016
DOI: 10.1111/acps.12607
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge, attitudes, social distance and reported contact regarding people with mental illness 2009–2015

Abstract: Objective: To investigate whether public knowledge, attitudes, desire for social distance and reported contact in relation to people with mental health problems have improved in England during the Time to Change (TTC) programme to reduce stigma and discrimination [2009][2010][2011][2012][2013][2014][2015]. Methods: Using data from an annual face-to-face survey of a nationally representative sample of adults, we analysed longitudinal trends in the outcomes with regression modelling using standardised scores of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 38 publications
(64 reference statements)
5
95
1
2
Order By: Relevance
“…This study found no evidence to suggest that employment status or familiarity with mental illness explain the relationship between small area-level deprivation and attitudes towards mental illness, despite both being associated with attitudes in univariable analyses. The latter findings are supported by previous research, which suggests that lower levels of employment are associated with worse attitudes and participants who are more familiar with mental health problems report more positive attitudes, in keeping with Allport's contact hypothesis whereby more positive attitudes form through contact with stigmatised groups [7,8,12,13,23]. Whilst there is evidence in the literature to suggest area deprivation is associated with employment status [24], there is no evidence that individuals who are more familiar with mental illness reside in less deprived areas.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…This study found no evidence to suggest that employment status or familiarity with mental illness explain the relationship between small area-level deprivation and attitudes towards mental illness, despite both being associated with attitudes in univariable analyses. The latter findings are supported by previous research, which suggests that lower levels of employment are associated with worse attitudes and participants who are more familiar with mental health problems report more positive attitudes, in keeping with Allport's contact hypothesis whereby more positive attitudes form through contact with stigmatised groups [7,8,12,13,23]. Whilst there is evidence in the literature to suggest area deprivation is associated with employment status [24], there is no evidence that individuals who are more familiar with mental illness reside in less deprived areas.…”
Section: Discussionsupporting
confidence: 83%
“…Several individual-level variables were included in this study. These were: (1) age (16-24, 25-34, 35-44, 45-54, 55-64, 65-74 and 75 + years) [7,8]; (2) sex (male and female) [7][8][9][10][11], (3) ethnicity (white, black, Asian and mixed/other) [7]; (4) closest person with a mental illness, as a marker of familiarity with mental illness (self, immediate family/partner, other family or friend, acquaintance, colleague or other, don't know anyone) [7,8,12,13]; (5) highest educational attainment (no qualifications; post-16 qualifications such as GCSEs; post-18 qualifications below degree level, including A Levels; and degree level qualifications or equivalent); (6) equivalised weekly income (£0-£233, £233-£369, £369-£532, £532-£852 and £852 +); and (7) employment status (foreman or supervisor; manager; self-employed; or employee not elsewhere classified) [8].…”
Section: Individual-level Variablesmentioning
confidence: 99%
See 3 more Smart Citations